Political trust in the age of coronavirus: experiences in Mukuru, Nairobi, Kenya - Murumba, Ruth N.; Pashayan, Angela R. (Frontiers in Political Science, 2024)
This paper examines declining political trust at the onset of the coronavirus pandemic in the informal settlements of Mukuru Kayaba, Mukuru kwa Njenga, and Mukuru kwa Ruben; part of the Mukuru Informal Settlement located in Nairobi, Kenya. The average resident lives on $1.90–$3.50/day with no financial security net. During the COVID-19 pandemic governmental restrictions on movement and business operations, residents of Mukuru living at the extreme poverty level were unable to meet their basic needs. Trust in government was diminished, made worse by excessive force from armed officers of the Provincial Administration. Using qualitative and quantitative data, this research concludes that the lack of state support during the pandemic has led to further decline of political trust from residents of Mukuru.